Allele frequencies at six candidate genes associated with growth and carcass quality traits in the Boer goats - Javanmard, Arash; Panandam, Jothi Malar; Sugnaseelan, Sumita; Yusoff, Khatijah (Academic Journals, 2010)
In the recent years, the Boer goat has gained popularity due to its rapid growth, excellent meat quality,good adaptation and kidding percentage and non-seasonal fertility. Boer goats have been imported in large numbers into Malaysia to enhance the local goat industry. Marker assisted selection (MAS) offers the potential of improving the efficiency of selection programs and a number of candidate genes have been identified for growth and meat quality traits. The objective of the present study was to analyze the alleles at six candidate genes for growth and meat quality traits in 40 purebred Boer goats using restriction fragment length polymorphism (RFLP). The results indicated polymorphisms in leptin1,leptin2, leptin3, calpastatin, myostatin, pituitary-specific transcription factor (POUF1) and stearoyl-coA desaturase (SCD) genes (PIC = 0.18 - 0.37). The monomorphic IGFBP3 (1) and IGFBP3 (2) showed the presence of only the alleles H1 and X1 respectively. The Boer goats showed high frequencies of allele B for calpastatin (0.54), allele T for Leptin3 (0.64) and allele T for POUF1 (0.68). These three alleles have been previously demonstrated as favourable alleles for growth and meat quality traits in cattle and goats. However, there are no reports on the favourable alleles at myostatin (MSTN), SCD and IGFBP3genes, although these have been identified as candidate genes for growth and meat quality. Evaluation of phenotypic records for growth and meat quality and test of the association between alleles/genotypes and the traits have to be carried out before any allele at these loci may be considered for use in selection programs for Boer goats.